Estágio de docência: vivências do/no ensino remoto - ARACATI, Danielle Santana (2024)
This text aims to report and reflect on the experience lived in the Teaching Internship II discipline of the Integrated Degree in Sciences, Mathematics and Languages (LIECML) of the Institute of Mathematics and Scientific Education (IEMCI), of the Federal University of Pará (UFPA). ). The internship classes took place synchronously and asynchronously. The first with the use of Google Meet and the second from guidelines and materials made available in a virtual classroom in Google Classroom. This discipline took place from March 15 to April 23, 2021, during Emergency Remote Teaching (UFPA/ERE2020). Therefore, we will report aspects of our participation in the internship, focusing on the development of teaching materials to be made available in remote teaching, as well as observations on how activities took place in a state public school in Belém-PA. Methodologically, it is a descriptive-exploratory study, with a qualitative approach (GODOY, 1995), with a reflection on the experience of records made in logbooks. From our observation, we realized that schools have been working with pedagogical resources for hybrid teaching, which in the context of the internship was characterized by the availability of printed materials and in digital format in WhatsApp groups. For the analysis, we used one of the activities designed for socialization in the participating school group. From our participation in the internship, we understand that professional teaching knowledge is temporal, plural, heterogeneous, personalized and situated and that it is necessary to pay attention to the unexpected, to adapt our performance in the classroom.